MEDIATION IN THE PROJECT PRESENT FATHER: : THE RECOGNITION OF INTEGRAL AFFILIATION IN THE LIGHT OF HUMAN DIGNITY. (Isagoge - Journal of Humanities and Social Sciences, 2022)
Civil registration and recognition of paternity are basic rights of any Brazilian citizen at birth. Registering the child at birth makes him/her a subject of rights, enabling him/her to act in society. However, these rights are not always realized, with a high rate of children not registered or with incomplete filiation. This finding led to the issue of Provision of the National Council of Justice 12/2010, which established the Present Father Project with the objective of changing this situation and encouraging the recognition of paternity of people without this registration, also seeking to ensure that the child enjoys the coexistence family and receive the parental care necessary for their full development. The article aims to highlight the relevance of inserting mediation in the flow of assistance to families in the process of acknowledging paternity, with the mediator facilitating the negotiations regarding care and coexistence in the family configuration established from the filial recognition and thus contributing to full acknowledgment of paternity.
Keywords: acknowledgment of paternity; civil registry; pai presente project; conflict mediation.